Profitability of Cocoyam Production and its Determinants in Cross River State, Nigeria - Mukaila, Ridwan; Falola, Abraham; Awoyelu, Festus EluwandeDurojaye; Akanbi, Sheu-Usman Oladipo; Chiemela, Chinedum Jachinma; Ukwuaba, Ikenna Charles; Ileka, Chikaosolu Maryqueen; Erim, Perpetua Agbor (Jordan Journal of Agricultural Sciences, 2022)
Neglected and underutilized crops can play a vital role in achieving food security as humans concentrate on consuming a few food crops which have increased in price over time. Understanding the profitability of these crops can enhance farmers’ decisions to grow them. Therefore, this study investigated cocoyam production profitability, factors responsible for its profitability, and the constraints faced in cocoyam production in Cross River State, Nigeria. Data collected primarily with the use of questionnaires were analysed with descriptive statistics, cost and return analysis, multiple regression and the Likert rating scale. The results revealed that the majority of cocoyam farmers were male, married, in their economically active age and operated on a small scale. Cocoyam production was a profitable venture as the farmers had a gross margin of N175, 822.45 (USD 428.04) per hectare of cultivated land with an operating ratio of 0.24 and a return on capital invested of 3.17. The factors that influenced the profitability of cocoyam production were education, household size, farm size, farm output, cooperative membership, access to credit and annual income. The major constraints faced in cocoyam production were inadequate access to credit, poor government support, high cost of inputs and poor storage facilities. To enhance cocoyam profitability, the study recommends the provision of farm inputs and financial support to inform of credit or grants to the farmers. This would not only increase their profit but also enhance the decision to increase production which will increase food availability and, in turn, reduce the problem of food insecurity.